Effect of coating time on LPP treated silk fabric coated with ZnO2 nanoparticles - Wattanaporn Intarasang (2018)
In this work, effect of coating time on coating of ZnO2 nanoparticles of Low Pressure Plasma (LPP) treated Local Thai Silk fabric was studied. The LPP with conditions of power 50 and 100 Watts at radio frequency of 13.56 MHz under argon atmosphere with the pressure of 100 mTorr and holding time for 5 minutes was treated on the surface of Local Thai Silk fabric. After LPP treatment, the fabric samples were coated with ZnO2 nanoparticles using dip coating technique for different time (5, 25, 45 and 60 minutes). From the results, it can be seen that coating time of 45 minutes exhibited the optimum coating of ZnO2 nanoparticles. Moreover, it was found that LPP treatment could enhance the hydrophobic of Local Thai Silk fabric when compared with that of untreated sample. Morphology of the samples was determined using scanning electron microscopy technique (SEM).